Nephroprotective potential of Polyalthia longifolia roots against vancomycin-induced renal toxicity in experimental animals - Das, Kuntal; Muthukumar, A.; Almuqbil, Mansour; Imran, Mohd.; Rabaan, Ali A.; Halwani, Muhammad A.; Garout, Mohammed; Alsaleh, Abdulmonem A.; Alissa, Mohammed; Alwashmi, Ameen S. S.; Alshehri, Ahmad A.; Alsayyah, Ahmed; et al. (Frontiers in Pharmacology, 2023)
This study was done to investigate the possible nephroprotective effect of an ethanolic root extract of Polyalthia Longifolia (PL) on vancomycin-induced nephrotoxicity using curative and protective models. Vancomycin (150 mg/kg, intravenous) was given to healthy Wistar albino rats in the curative model before the start of treatment, whereas the protective group received vancomycin at the conclusion of the 10-day treatment procedure. Animals were divided into six groups for both models; group I served as the normal control, while groups II, III, IV, V, and VI were kept as toxic control, standard (selenium, 6 mg/kg), LDPL (low dose of PL 200 mg/kg), HDPL (high dose of PL 400 mg/kg), and HDPL + selenium (interactive) groups, respectively. Renal biomarkers [(uric acid, creatinine, blood urea nitrogen (BUN), serum proteins], and blood electrolyte levels were measured for all tested groups. When compared to the vancomycin group, the HDPL significantly (p<0.01) showed greater effectiveness in lowering the BUN, potassium, and calcium levels. Additionally, in the curative model, there was a significant (p<0.05) decrease in the blood levels of uric acid, creatinine, BUN, potassium, and calcium in the animals who received the combination of selenium and HDPL. Both LDPL and HDPL did not provide any distinguishable effect in the protective model, but groups that received HDPL with selenium did provide detectable protection by significantly lowering their levels of uric acid, BUN, serum potassium, and total serum protein in comparison to the vancomycin control group. These findings indicate that, whether administered before or after renal damage is induced, the Polyalthia longifolia root extract provided only modest protection to nephrons, which require selenium support to prevent vancomycin-induced kidney damage.